A Mennonite in Russia : The Diaries of Jacob D. Epp, 1851-1880 - Epp, Jacob D. (Jacob Davidovich), 1820-1890 (Book collections on Project MUSE., 2013)
Epp's writings reveal a skilled and honest diarist of deep feelings, and tell a human story that no conventional historical account could hope to equal.